Expression of CAS/CSE1L, the Cellular Apoptosis Susceptibility Protein, Correlates With Neoplastic Progression in Barrett's Esophagus. Issue 8 (September 2018) - Jiang, Kun; Neill, Kevin; Cowden, Daniel; Klapman, Jason; Eschrich, Steven; Pimiento, José; Malafa, Mokenge P.; Coppola, Domenico
Abstract : Background: Identifying the molecular switch responsible for the neoplastic progression of Barrett's esophagus (BE) and initiation of adenocarcinoma (ADC) is clinically essential and it will have a profound impact on patient diagnosis, prognosis, and treatment. The cellular apoptosis susceptibility gene CAS/CSE1L is overexpressed in various cancers, including a rare report on esophageal ADC; however, its expression in BE neoplasia has not been addressed. Materials and Methods: We investigated the expression of the CAS/CSE1L protein immunohistochemically in 56 esophageal resection specimens for ADC arising in BE. For each specimen, a full representative section of the invasive ADC was selected to include, when possible, BE, low-grade dysplasia (LGD) and high-grade dysplasia (HGD). Samples were stained for CAS/CSE1L expression using a rabbit polyclonal antibody recognizing the N-terminus of human CAS/CSE1L. Protein expression levels were measured using the Allred semiquantitative scoring system. The data were evaluated using χ 2 statistical analysis. Gene expression Omnibus was queried for CAS/CSE1L and BE neoplasia. Results: We found minimal to absent CAS/CSE1L in all BE tissue samples; however, CAS/CSE1L was upregulated in 60% of LGD and overexpressed in HGD and ADC. The results were statistically significant ( P <0.05). The localization of CAS/CSE1L protein was nuclear in BE; it became nuclear and cytoplasmic in LGD and HGD, and predominantly cytoplasmic in ADC. A similar progressive increase was observed for CAS/CSE1L gene expression. Conclusion: These findings show changes in CAS/CSE1L during BE progression. CAS/CSE1L may represent a potential marker for dysplasia/carcinoma.